Students’ Understanding of Philosophical and Cultural Values of Yogyakarta's Special Status - Novianto, Victor; Mahmudhah, Fitri; Prihatin, Novianto Ari; Syed Marzuki, Sharifah Zannierah (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
This study investigates how well junior high school students in the Special Region of Yogyakarta (DIY) comprehend the philosophical and cultural principles that support the region's special autonomy. The 2024 study across four regencies and one city in DIY implemented a quantitative survey using structured questionnaires to gather data from around 200 participants. The study discovered that students show limited understanding of important cultural principles like Hamemayu Hayuning Bawana and Manunggaling Kawula Gusti that form the core of Yogyakarta’s identity. Students generally lacked knowledge about the region's governance since many participants did not recognize key historical and cultural aspects. Students' lack of knowledge provides a threat to traditional values, while modernisation and democratic concepts increase their sway. According to this study, in addition to teaching about local governance, schools ought to integrate Yogyakarta's philosophical underpinnings and historical history through their cultural curricula. The plan proposes community involvement programs to help young people deepen their connection to their cultural roots. Future generations risk losing connection to the region's distinct cultural identity if educational and preservation efforts remain ineffective, thereby threatening Yogyakarta special status.